PENGARUH CITRA MEREK DAN PERSEPSI KUALITAS TERHADAP NIAT PEMBELIAN ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING DI COFFEE SHOP “KARAKTER KOPI” DENPASAR - Kadek Silvia Natasya Febriyanti (STIE BIITM, 2020)
ABSTRACTThis research is based on the researcher's interest in the development and competition of thegrowing coffee shop business in the present era where Brand Image, Quality Perception,Customer Satisfaction, and Repurchase Intention are very important in the development ofthis business. The purpose of this study is to determine the indirect effect of brand image onrepurchase intentions through customer satisfaction and perceived quality of repurchaseintentions through customer satisfaction. The data used in this study are primary dataobtained from the results of distributing questionnaires to respondents